(untitled) (Universal International Scientific Journal, 2026)
In the context of a neuro-digital civilization, where a powerful flow of information, digital technologies, and global ideological influences increasingly affect the consciousness of young people, the role and significance of national upbringing are analyzed. The main objective of this research is to identify effective mechanisms for developing cognitive and ideological resilience among youth based on national values, traditions, and spiritual heritage. Kalit soʻzlar: kognitiv rezistentlik, mafkuraviy immunitet, axborot xavfsizligi, raqamli madaniyat, tanqidiy fikrlash ko‘nikmalari, yoshlar ijtimoiylashuvi.